Impact Assessment and Consumer Behavior: Russian Evidence; Innovation Management and Education Excellence Vision 2020: from Regional Development Sustainability to Global Economic Growth - Ryzhkova M. V. Marina Vyacheslavovna (2016, 2016)
Title screen